PENGARUH PELATIHAN TERHADAP TINGKAT PRODUKTIVITAS PEGAWAI PADA KANTOR SOSIAL, TENAGA KERJA DAN TRANSMIGRASI KABUPATEN SIDRAP - Nurlina Nurlina (AkMen JURNAL ILMIAH, 2014)
This study aims to determine the rare - rare development management personnel Do Social Welfare Office and Transmigration. Sidrap and the effect of training on productivity pegawaidengan method used was to determine the effect on employee training in increasing employee performance, we used quantitative analysis to the analysis of correlation coefficients. Discussion The results of the analysis Analysis of the effect of training on productivity improvement work resulted in figure 3.57 , which means that if the number of employees Sosila Office . Manpower and Transmigration who follow the training at the level of or to any person , the labor productivity will increase by 3.57 % .While analisisi results showed the correlation of 0.98 , which means it has a strong and positive relationship and the same direction, so that one of the variables up and down will be followed by an increase and a decrease in other variables .